Active geomorphic hazards in the Sâmbăta Valley, Făgăraș Mountains (Romania): a tree-ring based approach - Chiroiu, Patrick; Onaca, Alexandru; Matica, Andrei; Lopătiță, Iosif-Otniel; Berzescu, Oana (Geographica Pannonica, 2022)
The present study addresses, for the first time, the problem of spatio-temporal reconstruction of geomorphic processes using tree-rings in the Sâmbăta Valley (Romanian Carpathians). The dendrogeomorphic analysis was conducted in two different sites, one affected by snow avalanches and the other by rockfall. A total number of 130 Picea Abies were sampled in the two sites. The results yield 13 major snow avalanches between 1950 and 2020 and a return period of 3.3 years. The winters with the highest activity index were 1988, 1997 and 2012. The rockfall reconstruction highlights several years of intense activity: 1952, 1955, 2003 and 2012. Thus, the results of the present study provide evidence of active geomorphic processes in the studied area, indicating that tourists are highly exposed to geomorphic hazards, as both sites interfere with popular hiking trails. (Because Sâmbăta Valley is one of the most intensely frequented by tourists in the Făgăraș Mountains, it is a need for warning signs to be installed on the exposed trails.